Design Gas LPG Leak Detection System Based on Internet of Things - Sari*, Erika Lety Istikhomah Puspita; Agung Enriko, I Ketut; Melinda, Melinda (Universitas Syiah Kuala, 2023)
Gas leak detection systems are essential for ensuring the safety of people and property. The use of Internet of Things (IoT) technology in gas leak detection systems has become increasingly popular due to its ability to connect devices and collect data from various sources. In this paper, we propose the design and development of an LPG gas leak detection system based on IoT. The system uses LPG gas sensors to detect the presence of gas in the environment, a microcontroller to process the data and send it to the cloud, and a web-based dashboard to display the real-time gas concentration levels and send alerts to users in case of gas leakage. Liquefied Petroleum Gas is a tool that serves to anticipate the safety of a gas leak hazard that can cause explosion and harm to the soul and property. In this final assignment explains how to create a detection system using the MQ-2 gas sensor that is connected to the NODEMCU ESP8266 microcontroller which is then sent to Firebase where the data storage can be viewed in realtime and continued to the Android application, the application used is the MIT App Inventor that has been created to receive notifications in the event of a gas leak. Using a MQ-2 gas sensor with a standard value in the event of gas leakage above 200. This system has fulfilled the rules of the Internet of things because it uses the Internet to connect.